2022
DOI: 10.1002/adom.202102443
|View full text |Cite
|
Sign up to set email alerts
|

Simple Phenazine‐Based Compounds Realizing Superior Multicolored Emission

Abstract: are commonly found in Cu [3][4][5][6] and noble metal (e.g., Ir, Pt) complexes. [7][8][9][10][11][12] Comparing with fluorescence materials, the predominant advantage of phosphorescence materials is their internal quantum efficiency that can approach 100%. [13][14][15] However, high cost is a barrier which cannot be circumvented for commercial manufacture. Besides above two categories of materials, pure organic molecules, for instance, thermally activated delayed fluorescence (TADF) materials, are regarded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…For the synthesis procedures please refer to the previous work 14 and supporting information. On the one hand, we previously found that the oscillator strength of S 1 approaches zero if the dihedral angle is vertical, which means S 1 may no longer be an ideal emissive state.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the synthesis procedures please refer to the previous work 14 and supporting information. On the one hand, we previously found that the oscillator strength of S 1 approaches zero if the dihedral angle is vertical, which means S 1 may no longer be an ideal emissive state.…”
Section: Resultsmentioning
confidence: 99%
“…Kasha's rule 1 is extensively observed in luminescence fields, [2][3][4] such as in fluorescent molecular rotors, 3,5-8 bioimaging [9][10][11][12][13] and organic light-emitting diodes (OLEDs), [14][15][16][17] in which the excitons return to the ground state from the lowest singlet S 1 (for phosphorescence this process occurs from T 1 ). To date, most organic luminescent materials follow this rule and their photophysical properties can be precisely simulated using quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the host materials with carbazole units exhibit high energy level, conforming to the design strategy for blue or deep blue emitters. 23 However, when the acceptor unit is connected with stronger electron-donating donors, the compounds will undergo a serious red-shift due to the intramolecular charge transfer (ICT) effect, 24 which is unfavorable for the design of deep blue D–A type TADF materials. Therefore, introducing host materials with weak electron-donating ability into molecules is effective to limit the red-shift of deep blue TADF emitters.…”
Section: Introductionmentioning
confidence: 99%